Breaking the silence: navigating adolescent knowledge, attitude, and perception on substance abuse in Diyala Province, Iraq (Journal of Ideas in Health, 2024)
Background: Drug use often leads to a range of health risks, social complications, and involvement in criminal behavior. This study aims to investigate adolescents' understanding, opinions, and perspectives on substance abuse. Methods: Between October and December 2023, a cross-sectional study was undertaken in Diyala Province, Iraq. High school students were sampled using a multistage sampling technique. Bivariate analysis utilized independent sample t-tests and one-way analysis of variance (ANOVA). Additionally, a multivariable linear regression analysis was performed to predict factors associated with knowledge, attitudes, and perceptions. All statistical analyses were carried out using SPSS version 16.Results: The study encompassed 365 students, with a mean age (SD) of 17.5 (+ 8.2), predominantly male (57.3%). Overall accuracy rates for knowledge, attitude, and perception stood at 87.1%, 86.7%, and 88.7%, respectively. Approximately 5.2% of the sample reported cannabis (hashish) use. Regression analysis revealed significant associations between higher knowledge scores and male gender (p=0.002, 95% CI:0.341, 0.729), urban residency (p US$400 (p >0.0001, 95% CI:0.907, 1573). Attitudes toward drug abuse prevention were influenced by male gender and highly educated parental backgrounds (p
Keywords: Adolescent, Drugs, Substance, Abuse, Addicts, Knowledge, Attitude, Perception, Iraq